A concept of industrial development in the 1980s - White, Padraic A. (Statistical and Social Inquiry Society of Ireland, 1983)
I welcome the opportunity to speak under the auspices of such a distinguished forum as the Statistical & Social Inquiry Society of Ireland. My first introduction to the Society was through the well thumbed volumes of its annual proceedings stored in the recesses of the National Library in Kildare Street when studying for a University degree. The printed texts of the Society recall the great economic issues of years gone by and by virtue of the insights and research incorporated in the papers, they stand the test of time remarkably well. My sense of the Society's distinguished past induces in me a certain feeling of trepidation when invited in from "the field of play" to reflect on the dominant intellectual and executive preoccupation of my own career for the past twelve years. A symposium on Industrial Policy in Ireland at this time is most opportune. A major review of "Policies for Industrial Development" has been undertaken and recently published by the NESC which will be taken into account in deciding future directions in industrial policy. The severity of the current economic recession in Ireland coupled with the rise in population and unemployment has created a widespread desire for a new approach to creating more jobs. A new Government is expected to be formed shortly and will be confronted with the formulation of job creating policies.
Symposium on industrial policy in Ireland
Read before the Society, 2 December 1982
Keywords: Irish industrial development; Irish industrial policy; Irish Development Authority; Telesis Report; 314.15